2004
DOI: 10.1196/annals.1316.011
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Abnormality of Schizophrenia Revealed by DNA Microarray: Impact on Glial and Neurotrophic Gene Expression

Abstract: DNA microarrays with isotope labeling from gene-specific primers enable sensitive detection of rare mRNAs, including neurotrophin and cytokine mRNAs in the brain. Using high-quality RNA from postmortem brains, gene-expression profiles covering 1373 genes were assessed in the dorsoprefrontal cortex of schizophrenic patients and compared with those of nonpsychiatric subjects. Statistical analysis of the DNA microarray data confirmed the findings of a previous GeneChip study by Hakak et al. (Proc. Natl. Acad. Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 17 publications
3
43
0
2
Order By: Relevance
“…One of the most widely replicated groups of genes with altered expression in schizophrenia relate to oligodendrocyte function and myelination, oligodendrocytes being the myelinating cells in the brain (3)(4)(5)(7)(8)(9)(10)(11)(12). These data are compatible with the considerable evidence for altered myelination and oligodendrocyte function in schizophrenia (13).…”
supporting
confidence: 78%
“…One of the most widely replicated groups of genes with altered expression in schizophrenia relate to oligodendrocyte function and myelination, oligodendrocytes being the myelinating cells in the brain (3)(4)(5)(7)(8)(9)(10)(11)(12). These data are compatible with the considerable evidence for altered myelination and oligodendrocyte function in schizophrenia (13).…”
supporting
confidence: 78%
“…Several postmortem studies in schizophrenia have demonstrated reduced expression of oligodendrocyte-related genes, [17][18][19][20][21][67][68][69][70][71][72] some of which may be susceptibility genes for schizophrenia. 33,[72][73][74][75] Moreover, several studies have evidence for deficits in oligodendrocytes in the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…119,120 Consistent evidence for an oligodendrocyte dysfunction in the disease also emerged from two other studies, in which levels of gene expression were assessed in the prefrontal cortices of schizophrenic patients. 121,118 Tkachev et al 118 further reported significant downregulation of proteolipid protein1 (PLP1), which maps at chromosome Xq21.3-q22 and mediates axonal-glial interactions, oligodendrocyte transmembrane protein (CLDN11), which is the third most abundant myelin protein in the CNS after PLP1 and myelin basic protein (MBP). MBP was also found to be downregulated.…”
Section: Oligodendrocyte-related Genes Associated With Schizophreniamentioning
confidence: 99%